Prevalence and factors associated with attempts to quit and smoking cessation in Malaysia - Lim, Kuang Hock; Heng, Pei Pei; Nik Mohamed, Mohamad Haniki; Chieh, Huey Teh; Mohd Yusoff, Muhammad Fadhli; Miaw, Jane Yn Ling; Baharom, Nizam; Wee, Lei Hum; Chan, Caryn Mei Hsien; Ho, Bee Kiau; Md Haris Robson, Noor Zurani; Draman, Samsul; et al. (SAGE Publishing, 2019)
Smoking cessation significantly reduces risk of smoking-related diseases and mortality. This study aims to determine the prevalence and factors associated with attempts to quit and smoking cessation among adult current smokers in Malaysia. Data from the National E-Cigarette Survey 2016 were analyzed. Forty nine percent of current smokers had attempted to quit at least once in the past 12 months and 31.4% of the respondents were former smokers. Multivariable analysis revealed that current smokers with low nicotine addiction and aged below 45 years were more likely to attempt to quit smoking. Being married, older age group, and having tertiary education were significantly associated with smoking cessation. Only half of the current smokers ever attempted to quit smoking and only a third of smokers quit. Stronger tobacco control policies are needed in Malaysia to encourage more smokers to quit smoking. Improved access to cessation support for underprivileged smokers is also needed.